Analisis kemampuan scientific explanation siswa pada materi sistem pencernaan manusia menggunakan model explanation oriented lesson design - Yanti, Aulia Fuji; Riandi, Riandi; Supriatno, Bambang (Assimilation: Indonesian Journal of Biology Education, 2021)
The purpose of this research was to analyze students’ scientific explanation on the human digestive systems topic using explanation-oriented lesson-design model. This research was conducted with a descriptive research design, a total of 29 eighth grade students from a junior high school in Tasikmalaya were involved in this research. Samples were taken using a convenience sampling technique. The scientific explanation observed was written causal explanation. This research data was collected using test, observation and interview method. The result of this research indicates that the number of students who have scientific explanation ability in intermediate category was 66% (n = 19), basic category was 31% (n = 9), and the advanced category was 3% (n = 1). Therefore, it can be concluded that most of the abilitiy of eighth grade students’ scientific explanation were intermediate category. Overall, students could make the components of scientific explanataion referred to this research. However, the components explaining a phenomenon, most students can only explain a phenomenon using patterns that are commonly observed. In addition, the components explain the patterns in the data and processes that support the occurence of a phenomenon, most students explain the patterns and processes that support the occurence of the phenomenon with spesific, but not detailed. In addition, the components connect data patterns and processes using principles, theories, or disciplinary core ideas, most student connect data patterns and processes using principles by including relevant concepts that are logically, specific, but not detailed.